Analysis of Drag Torque Characteristic of Hydro-viscous Clutch with Consideration of Cavitation Effect - Sun Chunlian (Jixie chuandong)
In order to accurately predict the internal flow field and drag torque characteristics of the hydro-viscous clutch,with the flow field of double circular groove clearance as the research object,based on the principle of hydrodynamics and the Newtonian internal friction law,a two-phase flow CFD mathematical model considering cavitation effect is established,the fluid field is numerically simulated by FLUENT,and the influence of different rotational speed,inlet pressure and film thickness on field distribution,pressure distribution and drag torque characteristics are studied. The results show that the velocity distribution is inhomogeneous,and the fluid with the same direction of rotation has high velocity and has the function of diversion. The cavitation occurs in the intersection of the groove,the higher the speed,the larger the film thickness,the more the cavitation phenomenon. The high pressure region occurs at the entrance,and the pressure decreases with the radial direction,the negative pressure effect is generated at the outer edge. The bearing capacity is approximately linear with the rotation speed. The higher the rotational speed,the more obvious the shear stress increases. When the speed is less than（ 1 400 1 600） r/min,the drag torque is approximately linear with speed and then decreases slowly when reaching a certain peak. With the film thickness decreases,the drag torque is improved,and its peak point corresponds to a higher speed.